HARTMANN'S PROCEDURE REVISITED - CHOUBEY, RP (Med J Armed Forces India, 2001)
Between July 1991 and June 1999 out of 176 patients undergoing colonic surgery (elective and emergency), Hartmann's procedure was performed in 63. There were 39 males and 24 females. Mean age was 43 years (range 12 to 81). To assess the utility of Hartmann's procedure the documents of all these 63 patients were retrospectively analysed. In 47 bowel continuity was reestablished. The over all mortality in first stage operation (Hartmann's procedure) was 12.7% and mortality in the second stage procedure (reestablishing bowel continuity) was nil. Complication rate was drastically less in second operation. The authors conclude that Hartmann's procedure is safe and effective while dealing with colorectal pathologies as resection and primary anastomosis is fraught with danger.